2013
DOI: 10.1039/c2dt32009f
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembly between dicarboxylate ions and binuclear europium complexes: moving to water—pH dependence and effects of buffers

Abstract: Binuclear lanthanide complexes consisting of two lanthanide binding domains in kinetically stable DO3A binding pockets linked by a 3-functionalized meta-xylyl bridge form stable 1:1 adducts with isophthalate and dinicotinate in water. The influence of buffer, pH and ligand structure on the binding of dinicotinate has been investigated.The nature of the f-electron configurations of the trivalent lanthanide ions results in long lived, high intensity luminescence and strong paramagnetic perturbation of proton res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 28 publications
0
26
1
Order By: Relevance
“…Furthermore, the difference between these parameters in BBS and HEPES buffer strongly suggests that HEPES buffer is a competitive buffer in this system. Such effects have been observed for the pyridine‐bridged system, where HEPES is a more competitive ion than phosphate …”
Section: Resultsmentioning
confidence: 68%
See 2 more Smart Citations
“…Furthermore, the difference between these parameters in BBS and HEPES buffer strongly suggests that HEPES buffer is a competitive buffer in this system. Such effects have been observed for the pyridine‐bridged system, where HEPES is a more competitive ion than phosphate …”
Section: Resultsmentioning
confidence: 68%
“…5‐nitro‐α,α′‐(DO3Ayl)‐ m ‐xylene (H 6 ⋅ 1 ) and its binuclear europium complex (Eu 2 ⋅ 1 ) were prepared as previously described . Although this ligand was among the first m ‐xylyl‐bridged bismacrocycles to be prepared, we have previously only carried out very limited studies upon the binding of anionic guest species beyond establishing the affinity for dinicotinate in tris(hydroxymethyl)aminomethane (TRIS) buffer . In this study, we report a much broader range of data and establish the affinity for four different anions, and define the binding in methanolic and aqueous media at a range of temperatures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S5, ESI †), ¶ and concomitant changes in R 2 indicate the potential utility of these materials as 19 F contrast agents. [33][34][35][36] We postulated that effective ligation of ethoxy-fluorinated isophthalic acid analogues to binuclear gadolinium adducts would facilitate effective, and distance-optimised, PRE. 5 Recent investigations into the chelation of binuclear lanthanide chelates with dicarboxylate species have demonstrated that strongly bound adducts can be formed due to the unique binding pocket available, where both mono-and bi-dentate binding of carboxylate groups can occur with 7-coordinate lanthanide centres.…”
mentioning
confidence: 99%
“…2 and Table S1, ESI †). 34,37,38 These conformational changes will, of course, have direct consequences on the relaxation through self-assembly. Somewhat counter-intuitively, relaxometric characteristics were less strongly enhanced at high solution pH (9)(10)(11)(12) also.…”
mentioning
confidence: 99%